Fundamental concepts in digital preservation - Silva Júnior, Laerte Pereira da (2016)
The growing availability of digital information in repositories requires a new profile of information professional or curator, one who, among other aspects, master the fundamental concepts regarding digital preservation. In this paper, through a revision of the literature, we describe the bit preservation and functional preservation as fundamental concepts of the digital preservation problem. We recommend that public institutions should develop strategies to provide adequate training to raise this knowledge and awareness in order to assure that everyone who is involved in the production and curation of the digital preservation must have the profile needed to fulfil this function.